2011
DOI: 10.1016/j.biopsych.2011.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Inverted-U–Shaped Dopamine Actions on Human Working Memory and Cognitive Control

Abstract: Brain dopamine has long been implicated in cognitive control processes, including working memory. However, the precise role of dopamine in cognition is not well understood, partly because there is large variability in the response to dopaminergic drugs both across different behaviors and across different individuals. We review evidence from a series of studies with experimental animals, healthy humans and patients with Parkinson’s disease, which highlight two important factors that contribute to this large var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

153
1,331
9
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,481 publications
(1,499 citation statements)
references
References 156 publications
153
1,331
9
6
Order By: Relevance
“…However, other studies have found dose‐dependent effects of DRD2 C957T variant on both cognitive outcomes (e.g., Byrne et al., 2016) and on D2 receptor availability in both striatal (e.g., Hirvonen et al., 2005) and extrastriatal areas (e.g., Hirvonen, Lumme, et al., 2009), or even an inverted‐U‐shaped pattern in cognitive performance, whereby no significant difference in the performance between CC and TT genotypes was detected (Gurvich & Rossell, 2014). The absence of significant difference in the performance between CC and TT homozygotes in the current study may similarly suggest the inverted‐U‐shaped dopamine action, whereby intermediate levels of dopamine lead to superior cognitive performance (Cools & D'Esposito, 2011). Regardless of whether a recessive pattern or inverted‐U‐shaped pattern applies here, we believe that investigating genotype groups separately provides a more detailed picture of the nature of this gene variant — a model increasingly adopted by researchers in this area.…”
Section: Discussionmentioning
confidence: 66%
“…However, other studies have found dose‐dependent effects of DRD2 C957T variant on both cognitive outcomes (e.g., Byrne et al., 2016) and on D2 receptor availability in both striatal (e.g., Hirvonen et al., 2005) and extrastriatal areas (e.g., Hirvonen, Lumme, et al., 2009), or even an inverted‐U‐shaped pattern in cognitive performance, whereby no significant difference in the performance between CC and TT genotypes was detected (Gurvich & Rossell, 2014). The absence of significant difference in the performance between CC and TT homozygotes in the current study may similarly suggest the inverted‐U‐shaped dopamine action, whereby intermediate levels of dopamine lead to superior cognitive performance (Cools & D'Esposito, 2011). Regardless of whether a recessive pattern or inverted‐U‐shaped pattern applies here, we believe that investigating genotype groups separately provides a more detailed picture of the nature of this gene variant — a model increasingly adopted by researchers in this area.…”
Section: Discussionmentioning
confidence: 66%
“…In particular, people have shown systematic interindividual and intraindividual differences regarding the degree to which their performance reflects cognitive persistence and flexibility (Hommel, 2015;Hommel & Colzato, 2017a, b). Persistence and flexibility have been considered two antagonistic metacontrol strategies (i.e., strategies that control cognitive control; Goschke, 2003;Cools & d'Esposito, 2011) that can be considered as the extreme poles of a common metacontrol dimension (Hommel, 2015). Changing tasks and environmental conditions require continuous readjustments of the balance between persistence and flexibility, which induces intraindividual variability (Akbari Chermahini & Hommel, 2010;Dreisbach & Goschke, 2004;Herd et al, 2014;Müller et al, 2007), and people differ systematically with respect to the efficiency of the degree to which this balance can be achieved (Arbula, Capizzi, Lombardo, & Vallesi, 2016;Babcock & Vallesi, 2017; for a review, see Hommel & Colzato, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a dysfunction in dopamine systems is observed in pathological conditions associated with cognitive deficits such as Parkinson's disease or schizophrenia (Heinrichs and Zakzanis, 1998;Moustafa and Gluck, 2011;Tunbridge, et al, 2006). Moreover, psychopharmacological studies showed that administration of dopaminergic drugs could result in opposite effects on cognitive performance (Cools and D'Esposito, 2011), notably during working memory or set-shifting tasks (Kimberg, et al, 1997;Mattay, et al, 2003;Mehta, et al, 2000). Indeed, administration of dopamine drugs is associated with a positive or negative effect on cognition, depending on whether baseline cognitive efficiency level is low or high, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, administration of dopamine drugs is associated with a positive or negative effect on cognition, depending on whether baseline cognitive efficiency level is low or high, respectively. These findings lead Cools and Robbins [(Cools and Robbins, 2004); see also (Cools and D'Esposito, 2011)] to propose a model in which the relationship between cognitive performance and DA level follows an 'inverted-U-shaped' function, defining an optimal DA level for any given cognitive task.…”
Section: Introductionmentioning
confidence: 99%